2002
DOI: 10.1083/jcb.200203022
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength fluorescent speckle microscopy reveals coupling of microtubule and actin movements in migrating cells

Abstract: Interactions between microtubules (MTs) and filamentous actin (f-actin) are involved in directed cell locomotion, but are poorly understood. To test the hypothesis that MTs and f-actin associate with one another and affect each other's organization and dynamics, we performed time-lapse dual-wavelength spinning-disk confocal fluorescent speckle microscopy (FSM) of MTs and f-actin in migrating newt lung epithelial cells. F-actin exhibited four zones of dynamic behavior: rapid retrograde flow in the lamellipodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
170
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 24 publications
12
170
1
Order By: Relevance
“…The results obtained using two types of FSM images and phase contrast images in different cells were all remarkably similar in both flow structure and velocity magnitudes. We measured retrograde flow velocities in the lamellipodia in the range 1-3 m/min, comparable with those reported for other cell types (Salmon et al, 2002;Vallotton et al, 2003). In all cells analyzed, flow maps revealed a flow approximately perpendicular to the edge of the cell.…”
Section: Characterization Of Actin Flowsupporting
confidence: 63%
See 1 more Smart Citation
“…The results obtained using two types of FSM images and phase contrast images in different cells were all remarkably similar in both flow structure and velocity magnitudes. We measured retrograde flow velocities in the lamellipodia in the range 1-3 m/min, comparable with those reported for other cell types (Salmon et al, 2002;Vallotton et al, 2003). In all cells analyzed, flow maps revealed a flow approximately perpendicular to the edge of the cell.…”
Section: Characterization Of Actin Flowsupporting
confidence: 63%
“…Kymographs indicated anterograde movement of actin in the cell body ( Figure 1I, yellow arrow), converging with the lamellipodial retrograde flow at the lamellipodium/cell body junction, where myosin motors are believed to generate strong contractile forces (Verkhovsky et al, 1999a). The existence of such pronounced convergence zone also has been described in other, less motile cell types (Salmon et al, 2002;Vallotton et al, 2004).The information obtained in kymographs is, however, limited. Kymographs show the movement within the selected region and along the selected direction only.…”
mentioning
confidence: 96%
“…Anterograde flow of actin structures and convergence zone of the retrograde and anterograde flow are also thought to be a characteristic feature of migrating cells (Salmon et al, 2002). However, these features are not inherent to all motile systems.…”
Section: Discussionmentioning
confidence: 99%
“…Our tracking approach based on cross-correlation between small areas of the image produced similar results, further supporting the notion of the generality of the retrograde flow phenomenon. Anterograde flow of actin structures and convergence zone of the retrograde and anterograde flow are also thought to be a characteristic feature of migrating cells (Salmon et al, 2002). However, these features are not inherent to all motile systems.…”
mentioning
confidence: 99%
“…Despite this dependence on MTs dynamics, nuclear movement itself does not require a structured MTs cytoskeleton, as neurons treated with nocodazole still display actin condensations and nuclear movements. Previous work has shown that in migrating cells MTs and F-actin interact and affect each otherЈs organization and dynamics (Salmon et al, 2002). Microtubule network emanates from the centrosome toward the leading process and nucleus, forming in the later a cage-like structure (Rivas and Hatten, 1995).…”
Section: Discussionmentioning
confidence: 99%